Implementation of Waterfall Method Cooperative Saves Loans KMK Mekar Jaya Web-Based - Febriani Naibaho (Institute of Computer Science (IOCS), 2022)
Cooperative Saves Loans KMK Mekar Jaya requires a good and integrated data processing system to facilitate decision making and create good service standards. Especially if the data is related to finances and customers. Data and information that is easily accessed by the Simpan Pinjaman KMK Mekar Jaya Cooperative, employees, and customers are needed to support the performance of the cooperative concerned. This research discusses the savings and loan application program consisting of member input forms, lending forms, payment forms, member forms, and payment reports, the programming language used for this application program is the PHP programming language and MySQL Database with servers. This research is made through stages (1) Identification, namely identifying problems, (2) Understand, namely understanding the work of existing systems, (3) Analysis, namely analyzing the system, (4) Report, which is making a report on the results of the analysis.